Pendidikan Karakter Berbasis Al-Qur’an dan As-Sunnah - Muhamad Akip (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2019)
This nation is looking for and choosing an idea that can complete the basalak education, which is expected to be a solution and able to bring this nation to progress. In the midst of the ambiguity of society in the world of education, the new hope is with the coming of the era of character education sourced from the quran and hadith, through a character-based holistic concept and promoting nine pillars; love God and all his creation, independence and responsibility, honesty and trustworthy, diplomatic, respectful and polite, generous and helpful, confident and hardworking, leadership and justice, humble, tolerant, peaceful and united.